2018
DOI: 10.1186/s12879-018-3042-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing linkage to and retention in care among HIV patients in Uganda and identifying opportunities for health systems strengthening: a descriptive study

Abstract: BackgroundWhile antiretroviral therapy (ART) availability for HIV patients has increased dramatically in Uganda, patient linkage to and retention in care remains a challenge. We assessed patterns of engagement in care in 20 Ugandan health facilities with low retention based on national reporting.MethodsWe assessed patient linkage to care (defined as registering for pre-ART or ART care at the facility within 1 month of HIV diagnosis) and 6-month retention in care (having a visit 3-6 months after ART initiation)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 35 publications
4
51
0
Order By: Relevance
“…The scale-up of ART provision to lower-level facilities, which was earlier limited to the urban referral facilities, has made ART more accessible. There is a possibility that some patients who are recorded as lost to follow-up (LTFU), are receiving ART from other facilities or are actually dead [20,21]. Therefore, attrition of patients at facilities, may not necessarily reflect treatment cessation in HIV patients.…”
Section: Discussionmentioning
confidence: 99%
“…The scale-up of ART provision to lower-level facilities, which was earlier limited to the urban referral facilities, has made ART more accessible. There is a possibility that some patients who are recorded as lost to follow-up (LTFU), are receiving ART from other facilities or are actually dead [20,21]. Therefore, attrition of patients at facilities, may not necessarily reflect treatment cessation in HIV patients.…”
Section: Discussionmentioning
confidence: 99%
“…One of the primary study outcomes was linkage to care, defined as patients newly diagnosed with HIV who registered in pre-ART or ART care at the facility within 1 month of diagnosis. Adult patients who were diagnosed between December 25, 2015 and June 25, 2016 were sampled for inclusion in the pre-intervention period of the study and all pediatric patients diagnosed in that timeframe were included [ 21 ]. Due to budgetary constraints and for efficiency purposes given the large number of newly initiated patients, we did not collect data on all newly diagnosed patients but rather systematically sampled every xth patient on the testing register such that a minimum of 40 patients were sampled per facility and the smallest possible number of patients beyond that were sampled.…”
Section: Methodsmentioning
confidence: 99%
“…We set out to evaluate linkage to care among individuals testing positive for HIV and six-month retention in care in antiretrovial therapy (ART) patients before versus after rollout of the intervention. At baseline, we noted that linkage to care was quite low (approximately 50%) and that adolescents, females, and patients in more rural settings had lower linkage and retention [ 21 ]. This study provides a comprehensive assessment of a holistic but relatively low-cost intervention to improve outcomes in PLWHIV across age groups.…”
Section: Introductionmentioning
confidence: 99%
“…One study in Uganda found just 53% of patients linked into care (i.e. registered with a facility providing treatment) within 1 month of their HIV counselling and testing (HCT) session [ 17 ]. Using home-based testing with augmented counselling in Uganda, another study achieved 44% linkage into care [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, linkage into care may simply take time: people need to accept and adjust to the diagnosis, reconcile how to manage stigma and make practical arrangements [ 20 ]. This may be lengthened by unmet mental health needs, amongst other potential drivers including health system, community, financial, household and individual factors [ 17 , 20 , 21 ]. Mental health support may facilitate linkage by treating anxiety and depression, and addressing acceptance and stigma issues.…”
Section: Introductionmentioning
confidence: 99%